Digital Teaching Material Short Story Text for 4C Ability Development in SMA/MA - Yuliastuti, Dwi; Kusmana, Suherli; Gloriani, Yusida (PT Inovasi Pratama Internasional, 2025)
In the current era of globalization, educators and students are required to master and be able to apply technology in teaching and learning activities. Students are expected to not only learn knowledge and skills, but should be able to identify learning sources as material to be discussed. Quality teaching materials can certainly improve learning outcomes that are tailored to the learning objectives to be achieved and included in the educational curriculum. Information related to the material to be discussed can be obtained through digital teaching materials and accessed via the internet network. Students are expected to have critical thinking competence in learning process activities and be able to analyze the topics of learning material being taught by the teacher. Students are able to apply the knowledge learned in everyday life. The role of educators is very important in creating a quality education system in accordance with technological demands. Through the 4C skills (Critical Thinking, Collaboration, Communication and Creativity), namely critical thinking, collaboration, communication and creativity, it is hoped that it can help students improve the quality of science in all fields of formal education in SMA / MA. Flipbook digital teaching materials can be used directly in face-to-face classes or online via devices connected to the internet network. As an educator, you should be able to provide creative and innovative teaching materials to students.